2024
DOI: 10.1109/taffc.2023.3278707
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Context-Aware Inference of Engagement in HMI: A Survey

Abstract: Engagement is the process by which participants establish, maintain, and end their perceived connection. Automatic engagement inference is one of the tasks required to develop successful human-centered HMI applications. Engagement is a multi-faceted multimodal construct requiring high accuracy in interpretating contextual, verbal and non-verbal cues, making the development of an intelligent automated engagement inference system challenging. Existing surveys concentrate on specific application settings, and a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 173 publications
(323 reference statements)
0
0
0
Order By: Relevance
“…Goldberg et al [ 2 ] suggested that automated detected approaches are more efficient, accurate, and time-saving. Indeed, recent studies have characterized cognitive engagement as detecting students’ voices [ 12 ], texts [ 13 ], behaviors [ 14 ], etc. Such a perspective might provide a more precise and traceable insight into the visual components of cognitive engagement [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…Goldberg et al [ 2 ] suggested that automated detected approaches are more efficient, accurate, and time-saving. Indeed, recent studies have characterized cognitive engagement as detecting students’ voices [ 12 ], texts [ 13 ], behaviors [ 14 ], etc. Such a perspective might provide a more precise and traceable insight into the visual components of cognitive engagement [ 15 ].…”
Section: Related Workmentioning
confidence: 99%